From Triple to Quadruple Roles: Reconceptualising Women's Labour in Bali's Tourism Economy - Narottama, Nararya; Lu Chang,; Pranyaswari, Made Diah; Anom, I Putu (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The paper examines how Balinese women organise their work within a tourism economy shaped by cultural obligations and gendered expectations. Using constructivist grounded theory and fieldwork at the Sukawati Art Market, Bali, it advances a Quadruple Roles framework reconceptualising women's labour as comprising reproductive, productive, sociocultural, and spiritual dimensions. With Moser's triple-role model and Tri Hita Karana as sensitising concepts, in-depth interviews and participant observation allowed spirituality to emerge inductively as an analytically distinct dimension of labour. Evidence shows that ritual practices establish the moral legitimacy that structures household work, market participation, and community organisation, even amid constraints of patriarchy, limited capital, and market competition. By reconceptualising spiritual obligation as labour, the paper demonstrates that culturally embedded tourism economies operate within a moral economy rather than a purely market system, with implications for gender-sensitive destination governance and comparative research.
Keywords: Balinese women; quadruple roles; spiritual labour; Tri Hita Karana (THK); constructivist grounded theory; moral economy